UMPSA expands access to higher education by opening Off-Campus Learning Centre - Naqiah, Puaad (UMPSA, 2025)
PULAU PINANG, 22 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to move forward in strengthening strategic networks and expanding the reach of the country’s higher education through its wholly owned subsidiary, UMPSA Advanced, with the signing of a memorandum of agreement (MoA) with The Ship Campus in Pulau Pinang recently.